Processo de adsorção de naftaleno em soluções aquosas: uma abordagem multivariada - Frescura, Lucas Mironuk (2019)
Naphthalene is the PAH with the simplest chemical structure, it has two aromatic rings. Thus, it serves as a standard for studies concerning this class of compounds, which present potential prejudicial to human health and are one of the main contaminants of water. Adsorption is a widely used technique for the removal of PAHs, and in recent years, different adsorbent materials have been developed for this purpose. With this increase, it's necessary to establish standards in adsorption by statistical methods, in order to reduce costs, waste generation and research time. This work used data obtained from a wide literature review of the last four decades of naphthalene adsorption of aqueous solutions with different adsorbents, searching for the greatest possible information of process. From the data obtained, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were performed. PCA results it was observed that the surface area of the adsorbents and the initial concentration of naphthalene are the main factors that influence the adsorption capacity of the material, this information has a proven reliability level by the explained value of variance of the technique if of 70.57%. With HCA, it was possible to establish standards of the different classes of adsorbents based on their chemical similarities and the characteristics involved in the technique, presenting four groups of different similarities.Thus, the techniques of multivariate statistics were able to define similar behaviors in the processes studies with different adsorbent materials, so it is possible to use such techniques to facilitate the study of PAHs removal, especially naphthalene.